The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/j.1556-6678.2011.tb00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Wellness, Professional Quality of Life, and Career‐Sustaining Behaviors: What Keeps Us Well?

Abstract: A sample of 506 professional counselors who were members of the American Counseling Association completed measures of professional quality of life, career‐sustaining behaviors (CSBs), and wellness. Significant differences were found both within the sample based on caseload characteristics and between the participants and available norm groups. Counselors with high wellness scores engaged in more CSBs and reported higher positive professional quality of life factors (compassion satisfaction). Implications for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
116
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(130 citation statements)
references
References 29 publications
(45 reference statements)
11
116
2
1
Order By: Relevance
“…In contrast to the spiritual heights of successes with clients, providing mental health services can be a physically, psychologically, and emotionally exhausting endeavor when met with demands for productivity, challenging client populations, restricted program funding, requirements for short-term interventions, or personal life stressors. Preliminary research has indicated that individuals identifying as counseling students typically demonstrate a higher level of overall wellness when compared to the general population (Myers, Mobley, & Booth, 2003;Lawson & Myers, 2011); however, evidence has also emerged suggesting a negative relationship between overall wellness and the distress experienced during training (Lenz, Sangganjanavanich, Balkin, Oliver, & Smith, 2012;Smith, Robinson, & Young, 2007). These findings have promoted the contention submitted by some authors (Clark, Murdock, & Koetting, 2009;Lawson et al, 2007;Lenz & Smith, 2010;Meyer & Ponton, 2006;Roach & Young, 2007) that counselor education programs may not cultivate meaningful wellness practices and resilience among students.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…In contrast to the spiritual heights of successes with clients, providing mental health services can be a physically, psychologically, and emotionally exhausting endeavor when met with demands for productivity, challenging client populations, restricted program funding, requirements for short-term interventions, or personal life stressors. Preliminary research has indicated that individuals identifying as counseling students typically demonstrate a higher level of overall wellness when compared to the general population (Myers, Mobley, & Booth, 2003;Lawson & Myers, 2011); however, evidence has also emerged suggesting a negative relationship between overall wellness and the distress experienced during training (Lenz, Sangganjanavanich, Balkin, Oliver, & Smith, 2012;Smith, Robinson, & Young, 2007). These findings have promoted the contention submitted by some authors (Clark, Murdock, & Koetting, 2009;Lawson et al, 2007;Lenz & Smith, 2010;Meyer & Ponton, 2006;Roach & Young, 2007) that counselor education programs may not cultivate meaningful wellness practices and resilience among students.…”
Section: Introductionmentioning
confidence: 84%
“…Some authors have suggested that well counselors are more helpful to their clients than those experiencing distress and impairment (Lawson & Myers, 2011;Lawson, Venart, Hazler, & Kottler, 2007;Lenz & Smith, 2010;Meyer & Ponton, 2006). In contrast to the spiritual heights of successes with clients, providing mental health services can be a physically, psychologically, and emotionally exhausting endeavor when met with demands for productivity, challenging client populations, restricted program funding, requirements for short-term interventions, or personal life stressors.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…When counseling programs address impairment, personal counseling is often a central component to the remediation plan with which the counselor trainee must comply to remain enrolled in the program (McAdams & Foster, 2007). Counselor educators may be concerned that trainees are more vulnerable and need professional help to overcome their own struggles (McCarthy, 2008); will enter the professional field without addressing their longterm significant impairments and will harm their clients as a result (Lawson & Myers, 2011).…”
Section: Personal Counseling For Impaired Studentsmentioning
confidence: 99%
“…In the indivisible self model, the contextual factors included development factors as well as the influence of local, institutional, and global contexts (Myers & Sweeney, 2005, p.1 0-11 ). 13 Given the complex nature ofwellness, Lawson and Myers (2011) argue that the benefit of using a structured holistic model is that it ensures no facets of life are ignored or deemphasized. Using a more structured guide is especially important considering that so many facets of our lives are related to wellness and that changes in one area can lead to changes (positive or negative) in other areas of our lives.…”
Section: Risk Factorsmentioning
confidence: 99%